Le travail émotionnel des adolescents face au web affectif. L’exemple de la réception d’images violentes, sexuelles et haineuses - Sophie Jehel; Serge Proulx (Communiquer)
In this article, we propose to explain how the emotional functioning of web platforms affects teenagers’ relationship to web content through the emotions they can trigger and their individual readiness to receive them. We explore the gap between, on the one hand, the affects authorized and calculated by these platforms and, on the other hand, the emotions felt by individuals regarding the informational content that reaches them on these digital spaces. Our analysis relied on a threefold theoretical framework: the “digital labour” hypothesis, understood as putting Internet users to work; the “affective web” which stimulates this work by capturing attention and calculation of affects; and finally, the dimension of “panoptic surveillance” by making the images visible, which increases emotional tension. The emotional work of adolescents ultimately appears polysemic and difficult to interpret without the use of a plural analytical grid and a careful listening to individual experiences.